Migration of highly educated Belgian and Dutch Turks: ‘Young Brains’ of Turkey - Yilmaz, Sinem (Border Crossing, 2016)
The aim of this research is to reflect the social imaginaries of highly educated Turkish migrants on their migration to their parents’ home country. Based on fieldwork and interviews with 19 Turkish-origin Belgian and Dutch citizens in a post-migration setting, this study demonstrates their pre- and post-migration lifestyles, and propounds the way they attribute meaning to their movement. The gap between personal wills of the actors of migration and expectations of them clearly shows how policies are flawed in their considerations of socio-cultural and economic development through ‘development agents’.